Respuesta :
7(t-4)-2t=4(t-3)
multiply 7 and 4 by all in parentheses
(7*t) + (7*-4) - 2t= (4*t) + (4*-3)
7t -28 - 2t= 4t - 12
combine like factors
5t - 28= 4t - 12
add 28 to both sides
5t= 4t + 16
subtract 4t from both sides
t= 16
CHECK:
7(t-4)-2t=4(t-3)
7(16-4) - 2(16)= 4(16-3)
7(12) - 32= 4(13)
84 - 32= 52
52= 52
ANSWER: t= 16
Hope this helps! :)
multiply 7 and 4 by all in parentheses
(7*t) + (7*-4) - 2t= (4*t) + (4*-3)
7t -28 - 2t= 4t - 12
combine like factors
5t - 28= 4t - 12
add 28 to both sides
5t= 4t + 16
subtract 4t from both sides
t= 16
CHECK:
7(t-4)-2t=4(t-3)
7(16-4) - 2(16)= 4(16-3)
7(12) - 32= 4(13)
84 - 32= 52
52= 52
ANSWER: t= 16
Hope this helps! :)